Earth - Marshak, Stephen
The Fourth Edition of Earth: Portrait of a Planet provides the perfect balance between an authoritative, yet accessible text and a stunning narrative art program. This makes it the book of choice for instructors and students, who all have their own diverse styles of both teaching and learning. The Fourth Edition of this best-selling text constitutes a major revision, packed with recent updates and new features such as beautiful and innovative narrative figures, stimulating inquiry-based pedagogy, a tightened core narrative, hundreds of new photographs, and coverage of hot topics, like the March 2011 earthquake/tsunami that devastated Japan, the rare element crisis, the shifting price of oil, and the recent tornado outbreaks